Father' Role in Stunting Prevention During the First Thousand Days of Life in Blabak Village Kediri City - Noeraini, Ardina Rezky; Nurahmawati, Dhewi; Mulazimah, Mulazimah; Wulaningtyas, Eko Sri; Yanti, Entin Srihadi; Pingkan Listia Putri; Fennydiyan Marini (Edumedia Solution, 2026)
Chronic malnutrition during the first 1000 days of life can lead to stunting, a disease of growth failure. In Indonesia, 21.5% of toddlers had stunting in 2023. Kediri City's stunting prevalence dropped to 5.56%, with 13 toddlers in Blabak Village diagnosed with stunting in 2024. Parenting methods are one of the variables that affect stunting. A child's development is greatly influenced by the role of parents, especially their fathers. The role of parents (fathers) will be optimal if supported by good knowledge about their role in the family. The goal of this project of community service is to provide information on the importance of fathers' roles throughout the first 1000 days of life. Participatory Action Research (PAR) is the approach used. The results of the community service project in Blabak Village, Kediri City, provided that an increase in knowledge about the significance of fathers' roles during the first 1000 days of life in an attempt to prevent stunting. Through the family's participation, this activity can indirectly reduce the incidence of stunting.